Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1099/00221287-91-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy and Laboratory Identification of Actinomyces and Arachnia and some Related Bacteria

Abstract: SUMMARYA numerical taxonomic study was made on 49 facultative anaerobic Grampositive filamentous and/or diphtheroidal organisms isolated from dental plaques, carious dentin and faeces, together with 63 reference strains belonging to the genera Actinomyces, Arachnia, B$dobacteriurn, Actinobacterium, Propionibacterium, Eubacterium and Lactobacillus. They were examined for 90 unit characters covering a wide range of tests and properties. The data were subjected to computer analysis in which the simple matching co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 63 publications
2
28
1
Order By: Relevance
“…A. naeslundii and A . viscosus are closely related phenotypically, demonstrating about the same degree ofrelatedness in numerical studies as the two serotypes of A. israelii do (10). Rodent strains of A. viscosus are different from human isolates serologically and in some other ways.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…A. naeslundii and A . viscosus are closely related phenotypically, demonstrating about the same degree ofrelatedness in numerical studies as the two serotypes of A. israelii do (10). Rodent strains of A. viscosus are different from human isolates serologically and in some other ways.…”
mentioning
confidence: 83%
“…Rodent strains of A. viscosus are different from human isolates serologically and in some other ways. Simply combining A. naeslundii and A. viscosus into a single species does not appear to solve the problem since subclusters within each species occur in numerical studies (9,10,16). Deoxyribonucleic acid (DNA)-DNA homology studies support division of A. naeslundii and A .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…viscosus and A . naeslundii has been recognized previously in serological (Collins et al, 1973;Holmberg & Forsum 1973;Gerencser & Slack, 1967) and numerical taxonomic (Holmberg & Nord, 1975;Fillery et al, 1978; studies. confirmed that these were independent, although closely related, species ;Coykendall & Munzenmaier (1979) reached the same conclusion in a study of DNA reassociation values.…”
mentioning
confidence: 98%
“…Institute Anaerobe Laboratory Manual (Holdeman, Cato and Moore, 1977;Loesche andGibbons, 1965, Holmberg andNord, 1975;Holbrook, Duerden and Deacon, 1977;Facklam, 1977;Komman and Loesche, 1980 On primary isolation plates, BPB could easily be detected due to their brown pigmentation and their colony morphology. They grow as highly convex and entire colonies, with a diameter of 1 to 2 mm., whereas the also pigmented A. odontolyticus appears as a very flat entire colony with a more reddish brown pigment and a diameter of 2-3 rom.…”
Section: D) Identificationmentioning
confidence: 99%